1976
DOI: 10.1111/j.1524-4725.1976.tb00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermabrasion for Showers of Seborrheic Keratoses

Abstract: Seborrheic keratoses, skin tumors of undetermined etiolo gy, are easily traumatized with consequent local irritation and inflammation, and are cosmetically undesirable. They can occasionally undergo malignant degeneration. A rapid increase in size and number of these lesions is thought by many to be a sign o f internal malignancy. Dermabrasion using a diamond fraise is a simple and fast method for removing multiple seborrheic keratoses with minimal trauma, rapid healing, and good cosmetic results.Seborrheic ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Dermabrasion has commonly been utilized for correction of cutaneous scars and removal of tattoos but is also useful for removal of superficial cutaneous lesions 1 . This method is best applied to lesions that do not extend below the papillary der‐mis, such as lentigines, verrucous nevi, epidermal nevi, actinic keratosis, and seborrheic keratosis 2 . Trichoepitheliomas, syringomas, adenoma seba‐ceum, and Darier's disease have also been treated by dermabrasion with varying degrees of success 3, 4 …”
Section: Discussionmentioning
confidence: 99%
“…Dermabrasion has commonly been utilized for correction of cutaneous scars and removal of tattoos but is also useful for removal of superficial cutaneous lesions 1 . This method is best applied to lesions that do not extend below the papillary der‐mis, such as lentigines, verrucous nevi, epidermal nevi, actinic keratosis, and seborrheic keratosis 2 . Trichoepitheliomas, syringomas, adenoma seba‐ceum, and Darier's disease have also been treated by dermabrasion with varying degrees of success 3, 4 …”
Section: Discussionmentioning
confidence: 99%
“…9 Over the next 20 years, dermabrasion was applied to many cutaneous conditions beyond just scars and acne pits, conditions that produce irregularities of the skin such as acne rosacea, rhinophyma, seborrheic keratoses, sebaceous hyperplasia, fibrous tumors of tuberous sclerosis, and discoid lupus erythematosus, just to name a few. 10,11,12,13,14 It was also widely applied in the removal of tattoos. 15 During this period, histological studies showed the significant dermal remodeling that takes place, an effect that is comparable to that seen in laser and deep peels.…”
Section: Dermabrasionmentioning
confidence: 99%